Incomplete resection of colorectal polyps of 4–20 mm in size when using a cold snare, and its associated factors - von Renteln, Daniel; Djinbachian, Roupen; Benard, Florence; Barkun, Alan N.; Bouin, Mickael; Bouchard, Simon; Deslandres, Érik; Panzini, Benoit; Sidani, Sacha; Leduc, Raymond; Jobse, Bruce C.; Pohl, Heiko (Endoscopy, 2023)
Background Cold snare polypectomy (CSP) is increasingly used for polypectomy and is recommended as the first-line modality for small (< 10 mm) polyps. This study aimed to evaluate incomplete resection rates (IRRs) when using CSP for colorectal polyps of 4–20 mm.Methods Adults (45–80 years) undergoing screening, surveillance, or diagnostic colonoscopy and CSP by one of nine endoscopists were included. The primary outcome was the IRR for colorectal polyps of 4–20 mm, defined as the presence of polyp tissue in marginal biopsies after resection of serrated polyps or adenomas. Secondary outcomes included the IRR for serrated polyps, ease of resection, and complications.Results 413 patients were included (mean age 63; 48 % women) and 182 polyps sized 4–20 mm were detected and removed by CSP. CSP required conversion to hot snare resection in < 1 % of polyps of < 10 mm and 44 % of polyps sized 10–20 mm. The IRRs for polyps < 10 mm and ≥ 10 mm were 18 % and 21 %. The IRR was higher for serrated polyps (26 %) compared with adenomas (16 %). The IRR was higher for flat (IIa) polyps (odds ratio [OR] 2.9, 95 %CI 1.1–7.4); and when resection was judged as difficult (OR 4.2, 95 %CI 1.5–12.1), piecemeal resection was performed (OR 6.6, 95 %CI 2.0–22.0), or visible residual polyp was present after the initial resection (OR 5.4, 95 %CI 2.0–14.9). Polyp location, use of a dedicated cold snare, and submucosal injection were not associated with incomplete resection. Intraprocedural bleeding requiring endoscopic intervention occurred in 4.7 %.Conclusions CSP for polyps of 4–9 mm is safe and feasible; however, for lesions ≥ 10 mm, CSP failure occurs frequently, and the IRR remains high even after technical success. Incomplete resection was associated with flat polyps, visual residual polyp, piecemeal resection, and difficult polypectomies.